ELECTRONIC DEVICES FOR CONTROLLING LOCAL POWER TRANSMISSION SYSTEM MODES (American Journal of Technology and Applied Sciences, 2025)
This article studies the types, functional capabilities and practical effectiveness of electronic devices designed for automated control of modern operating modes of local energy transmission systems. The study highlights devices developed on the basis of microprocessor systems, their role in monitoring, analysis and continuous control. The article is based on technological solutions that can be used in the lower links of large power grids.